A longitudinal study of the emerging self from 9 months to the age of 4 years - Kristen-Antonow, Susanne; Sodian, Beate; Perst, Hannah; Licata, Maria (Frontiers in Psychology, 2015)
The aim of this study was to investigate if children’s early responsiveness towards social partners is developmentally related to their growing concept of self, as reflected in their mirror self recognition (MSR) and delayed self recognition (DSR). Thus, a longitudinal study assessed infants' responsiveness (e.g., smiling, gaze) towards social partners during the still-face task and a social imitation game and related it to their emerging MSR and DSR. Thereby, children were tested at regular time points from 9 months to 4 years of age. Results revealed significant predictive relations between children’s responsiveness towards a social partner in the still-face task at 9 months and their MSR at 24 months. Further, interindividual differences in children’s awareness of and responsiveness towards being imitated in a social imitation game at 12 months proved to be the strongest predictor of children’s DSR at 4 years, while some additional variance was explained by MSR at 24 months and verbal intelligence. Overall, findings suggest a developmental link between children’s early awareness of and responsiveness towards the social world and their later ability to form a concept of self.